EVALUASI KONDISI LINGKUNGAN PERAIRAN KEPULAUAN SERIBU - Sachoemar, Suhendar I (BPPT)
An evaluation of the environmental situation of the Seribu Islands water ecosystem was conducted byusing the physical and chemical data obtained from various sources. The water quality of the Seribu Islandin general was within the range of moderate to good quality with indication poor trend in the southern partdue to relatively high turbidity as shown by lower transparency and high of the heavy metal concentrationof the Cd and Pb. The situation recommends that the aquaculture activities should be directed to themiddle and northern part of Seribu Island to ensure their sustainability.